THE IMPACT OF FINANCIAL TECHNOLOGIES (FINTECH) ON THE DEVELOPMENT OF ISLAMIC BANKING INSTRUMENTS IN ALGERIA: AN ANALYTICAL STUDY IN LIGHT OF BANKING DIGITAL TRANSFORMATION - Louafi Rabah (International Journal of Innovative Technologies in Social Science, 2024)
This article deals with an analysis about the impact of Financial Technologies (FinTech) in the development of Islamic banking instruments in Algeria, starting from establishing the theoretical concepts and the methodological challenges, and reaching to an evaluation of the reality of the local application and observing the digital transformations inside the Islamic banking sector. Also, the research reviews some models of international integration between financial technology and Islamic products, and it clarifies the most important legislative and technical obstacles that stand against integrating the digital solutions inside the Algerian banks. The article tries to show the effect of FinTech in improving the financing and the management of the Islamic investment and saving products, with looking forward the horizons of future innovation and the expansion of financial inclusion.